Optimal structure of a distributed grid metasheduler - Semenov, D.V.; Korneev, V.V. (Numerical Methods and Programming (Vychislitel’nye Metody i Programmirovanie), 2012)
An approach to choosing a tree-like structure of a metasheduler is considered to provide the grid resource allocation of a given job stream.